Truncus Arteriosus Type 1: A Prenatal Diagnosis, Case Report, and Literature Review - Alireza Golbabaei; Sara Memarian; Mahsa Naemi; Azade Rastgar; Rana Karimi; Behdad Gharib; Mohamad Taghi Majnoon (Mazandaran University of Medical Sciences, 2021)
Common arterial trunk (persistent truncus arteriosus) is a rare, congenital heart anomaly and characterized by Ventricular Septal Defect (VSD), single truncal valve, and a common ventricular outflow tract. We reported a case of truncus arteriosus type 1 in the fetus of a 28 years-old G2-P1-L1 pregnant female at 24 weeks of gestational age with large sub truncul VSD, truncal overriding, and main pulmonary artery bifurcation to the right and left pulmonary arteries.